ENGLISH FOR BUSINESS MANAGEMENT’ STUDENTS: NEED ANALYSIS IN ENGLISH FOR SPECIFIC PURPOSES (ESP) - Mega Fitri Wulandari (Institut Agama Islam Negeri (IAIN) Bone, 2023)
The purpose of this research is to investigate the students need in learning English for specific purposes (ESP) of the students in Business Management Study Program. This research employs descriptive and qualitative approach. The questionnaire and interview are the only instrument used in this research. The questionnaire distributed to the student that has an answer which can be directly selected and the interview aims to collect more information related to the questionnaire. The participants of this study are the fourth semester of business management students in the Politeknik Negeri Manado in the academic year 2022-2023. The total of the business management students are 60 students who were or had completed general Basic English. The result indicate that students’ main purpose in learning English are for study/education and students’ needs of language proficiency skill are speaking. The students’ needs of the English sub-skills materials are related to the job vacancy, listening to the movies/songs/drama/role play, present a business plan for the speaking material and chose business letter/ job application letter for writing material. In the other hand, grammar knowledge and vocabulary mastery also needed by the student.